Beyond traditional supply chain management: Addressing sociopolitical challenges in increasingly turbulent global trade landscape - Narkhede G.; Samuel C.; Mahajan S.; Verma D.; Sakhare N.; Chaudhari T. (My University, 2025)
An increasing number of sociopolitical issues, including international wars, armed conflicts, decoupling of economic powers, deglobalization, nationalism, protectionism, sanctions, tariff wars, political tensions, and other sociopolitical forces affecting global supply chains (GSCs) and supply chain management (SCM) strategies. Amidst these sociopolitical factors, the global trade landscape is undergoing a seismic shift. This paper examines the complex web of these sociopolitical aspects, their impact on SCM strategies, and their implications for GSCs. The systematic literature review approach is used for this research, which entails the following steps: selecting and assessing pertinent sources, summarizing and synthesizing the literature, examining challenges and opportunities, articulating conclusions, and pinpointing prospective directions for future research. The findings of this study reveal that these sociopolitical factors have significant impacts on multiple facets of SCM, such as sourcing strategies, supplier relationships, risk management, and overall supply chain resilience. In addition, the study presents a roadmap for businesses to effectively navigate these difficulties, which involves diversifying supply chain networks, integrating corporate sustainability strategies, and implementing environmental, social, and governance factors into business operations. The originality of this research lies in its integrated and holistic approach to the integration of sociopolitical factors into SCM theory and practice. © 2024 ERP Environment and John Wiley & Sons Ltd.